(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2025)
Nowadays, in the process of industrial development and the introduction of modern technologies, the welding industry is gaining importance. It is impossible to imagine all the existing production enterprises in our republic without welding, and the demand for welders is also increasing.